The endowment effect in groups with and without strategic incentives - Andreas Glöckner; Janet Kleber; Stephan Tontrup; Stefan Bechtold (Max Planck Institute for Research on Collective Goods, 2009)
The realization of market transactions often depends on decisions in groups in which members are anonymous and cannot communicate, but have interrelated outcomes. In a comprehensive study, we investigated the interaction of group effects, strategic effects and endowment effects in different group situations. We show that groups display an endowment effects for uncertain goods which is reduced by about 50% compared to the endowment effect in individuals in corresponding situations. In group situations with additional strategic incentives to overprice the endowment effect completely diminished. The strategic effects and group effects on pricing in group situations cannot be found for participants' personal valuations of the good, whereas the endowment effect for personal valuations prevailed in both group conditions. This indicates that the endowment effect might be more fundamental than group effects and strategic effects. A paramorphic model for pricing in strategic group situations is suggested and practical implications are discussed.
Keywords: 330; Endowment Effects; Decision Making; Groups; Strategic Incentives